Renal microcirculation and mechanisms in diabetic kidney disease - Hang, Xing; Ma, Jiang; Wei, Yu; Wang, Yayun; Zang, Xiaoyu; Xie, Pengfei; Zhang, Lili; Zhao, Linhua (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD), a severe and long-term complication of diabetes, is a microcirculatory pathology influenced by diabetes-related factors that affects hundreds of millions of people worldwide. DKD is characterized by proteinuria, glomerular injury, and renal fibrosis, ultimately leading to end-stage renal disease. Its pathogenesis is complex and involves multiple cellular and molecular mechanisms. Microcirculatory disorders form the fundamental pathological basis of DKD. These disorders are primarily manifested through changes in the number and structure of renal microvessels, alterations in renal hemodynamics, formation of renal thrombi, glomerular endothelial cell dysfunction, and associated lesions in podocytes and mesangial cells. This article focuses on renal microangiopathy and glomerular endothelial cell (GEC) dysfunction, summarizing the mechanisms associated with microcirculatory lesions in DKD, including nitric oxide (NO), advanced glycation end-products (AGEs), vascular endothelial growth factor (VEGF), the renin-angiotensin-aldosterone system (RAAS), reactive oxygen species (ROS), the NLRP3 inflammasome, protein kinase C (PKC), epidermal growth factor receptor (EGFR), and platelet-derived growth factor (PDGF). Additionally, we briefly introduce the characteristics of DKD animal models in terms of renal microcirculation and discuss the application of relevant technological tools in studying microcirculatory lesions in DKD.